Evaluation of ADEOS AVNIR data for land cover classification in the Mount Pinatubo area - Paringit, Enrico C. (1999)
Disasters require continuous monitoring in order to thwart their potential threats to life and property. By providing periodically acquired remotely-sensed data, information on landcover change will aid planners and decision makers in planning for future land use as a means to mitigate potential hazards. The Mount Pinatubo area, which is under constant threat from lahar remobilization in Central Luzon, requires such attention. In conjunction, there is a need to develop appropriate techniques to process remotely-sensed data from new satellite payloads. The ADEOS AVNIR sensor, launched in 1997 by NASDA, is designed spatially and spectrally different with that of its predecessors. An assessment of its application potentials must be foremost undertaken. This study sought to determine the capability of ADEOS AVNIR data for landcover classification by examining its geometric and thematic accuracy qualities. The study took special consideration of the fact that the study area is within the lahar hazard zone. Likewise, this study investigated the effects of multisensor techniques to the enhancement of landcover classification, specifically by merging JERS-1 SAR with ADEOS AVNIR by the IHS color transformation and subsitution methods. Results show that ADEOS AVNIR imagery fulfills basic geometrical requirements for landcover mapping at a convenient scale of 1 : 80,000. ADEOS AVNIR was effectively decorrelated by its fusion with the JERS-1 SAR data, providing better perceptibility and interpretability. Standard supervised classification of ADEOS AVNIR data yields an 87% overall accuracy and a KHAT of 0.8350. Both the original and the fused datasets agree on the type of landcover which is difficult to discriminate but are in dissension as to the easiest landcover to discriminate. Furthermore, statistical test show that the improvement in classification was not significant enough to cause any change in the use of the classification data. Thus, given the choice, one should choose the faster, more practical, simple and efficient approach, considering that the type of imagery to be classified would not be a factor.
Thesis (M.S. Remote Sensing)--University of the Philippines Diliman.
Keywords: Aerial photography in land use -- Philippines -- Mt. Pinatubo (Zambales); Land use -- Planning; Remote sensing -- Philippines -- Mt. Pinatubo (Zambales)